Evaluation of Formaldehyde When Complete Feed and Soybean Meal Were Inoculated with Porcine Epidemic Diarrhea Virus, Porcine Reproductive and Respiratory Syndrome Virus, and Seneca Valley Virus 1 - Olivia L. Harrison; Jianfa Bai; Martee Larson; Roman M. Pogranichniy; Francisco Domingues; Nicole Holcombe; Othmar Lopez; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2024)
Chemical mitigants have been found to decrease virus concentrations in feed and ingredient matrices. Continued research is needed to identify the appropriate inclusion levels and application time for different viruses in these matrices. Therefore, the objective was to evaluate different inclusion levels of formaldehyde when applied either pre- or post-inoculation of porcine epidemic diarrhea virus (PEDV), porcine reproductive and respiratory syndrome virus (PRRSV) and Seneca Valley virus 1 (SVV1) to complete feed or soybean meal. The experiment was designed in a 2 × 2 factorial with a formaldehyde-based product (Termin-8, Anitox Corp. Lawrenceville, GA) applied either before virus inoculation (pre-inoculation) or after inoculation (post-inoculation) at either a 4 or 6 lb/ton. On d 0, samples of the respective matrices were weighed in 50 g aliquots and added to 500 mL bottles. Chemical mitigants were applied to the pre-inoculation samples at their respective inclusion levels and 50 μL each of 1×107 TCID50/ mL PEDV, 1×108 TCID50/mL PRRSV, and 1×108 TCID50/mL SVV1 were added to the post-inoculation samples. All bottles were shaken and allowed to sit at room temperature for 24 hours. On d 1, virus was added to the pre-inoculation samples and chemical mitigants were added to the post-inoculation bottles. Half of the samples were immediately processed (0 hr) and the other half were incubated at room temperature for an additional 24 hours (24 hr). Samples were processed and aliquots were analyzed via a triplex PCR assay at Kansas State University Veterinary Diagnostic Laboratory. Cycle threshold and proportion PCR positive were analyzed using SAS GLIMMIX v 9.4 (SAS, Inc., Cary, NC) with each virus and matrix combination analyzed individually. An application time × inclusion level interaction was observed for PEDV at 0 hr and SVV1 and PEDV at 24 hr in complete feed, where less viral RNA (P < 0.05) was detected in the post-inoculation samples at either inclusion level as compared to the positive controls. In soybean meal, the same interaction was observed in PEDV and PRRSV at 0 hr and SVV1 and PEDV at 24 hr with less detectable RNA observed (P < 0.05) in the post-inoculation samples regardless of inclusion level than the pre-inoculation counterparts and the controls. Overall, an application time effect was noticed in each matrix where less RNA was detected in the post-inoculation samples at 0 hr (P < 0.05) compared to the pre-inoculation samples and the control, and at 24 hr, both the pre- and post-inoculation samples had less detectable RNA (P < 0.05) than the control. Overall, formaldehyde can reduce detectable RNA immediately in both contaminated complete feed and soybean meal, with greater decreases observed as mitigant contact time increases.
Keywords: formaldehyde; soybean meal; virus